Mechanical and nuclear shielding properties of sodium cadmium borate glasses: Impact of cadmium oxide additive. Issue 3 (15th February 2020) - Saddeek, Yasser B.; Issa, Shams A.M.; Alharbi, T.; Aly, K.; Ahmad, Mahmoud.; Tekin, H.O.
Abstract: In this study, highly effective radiation shielding glass materials with different amount of CdO additive were investigated in terms of nuclear shielding performance. Moreover, mechanical properties have been determined. The μm values were computed using XCOM and XMuDat program. The gamma and neutron shielding parameters such as μm, HVL, Zeff, EBF, EABF, SAFE, bco, bico, σco and σabs are calculated to understand the radiation shielding performances of investigated glasses. The results show that μm, Zeff and σabs values increase as the CdO content increases. The S7 sample has the lowest HVL, MFP, EBF, EABF, SAFE, bco, bico and σco values. Therefore, S7 glass sample (70 mol% of CdO) which has also the highest number of bonds per unit volume can be considered as a superior material for radiation shielding applications. The outcomes of this study can be very useful for future applications of investigated glass materials in medical and industrial radiation fields.